Genetics and epigenetics of Pinus nigra populations with differential exposure to air pollution - Katsidi, Elissavet Ch.; Avramidou, Evangelia V.; Ganopoulos, Ioannis; Barbas, Evangelos; Doulis, Andreas; Triantafyllou, Athanasios; Aravanopoulos, Filippos A. (Frontiers in Plant Science, 2023)
Forest species in the course of their evolution have experienced several environmental challenges, which since historic times include anthropogenic pollution. The effects of pollution on the genetic and epigenetic diversity in black pine (Pinus nigra) forests were investigated in the Amyntaio – Ptolemais – Kozani Basin, which has been for decades the largest lignite mining and burning center of Greece, with a total installed generating capacity of about 4.5 GW, operating for more than 70 years and resulting in large amounts of primary air pollutant emissions, mainly SO2, NOx and PM10. P. nigra, a biomarker for air pollution and a keystone species of affected natural ecosystems, was examined in terms of phenology (cone and seed parameters), genetics (283 AFLP loci) and epigenetics (606 MSAP epiloci), using two populations (exposed to pollution and control) of the current (mature trees) and future (embryos) stand. It was found that cone, seed, as well as genetic diversity parameters, did not show statistically significant differences between the exposed population and the control. Nevertheless, statistically significant differences were detected at the population epigenetic level. Moreover, there was a further differentiation regarding the intergenerational comparison: while the epigenetic diversity does not substantially change in the two generations assessed in the control population, epigenetic diversity is significantly higher in the embryo population compared to the parental stand in the exposed population. This study sheds a light to genome dynamics in a forest tree population exposed to long term atmospheric pollution burden and stresses the importance of assessing both genetics and epigenetics in biomonitoring applications.